2010
DOI: 10.1111/j.1468-3083.2010.03664.x
|View full text |Cite
|
Sign up to set email alerts
|

A cost analysis of photodynamic therapy with methyl aminolevulinate and imiquimod compared with conventional surgery for the treatment of superficial basal cell carcinoma and Bowen’s disease of the lower extremities

Abstract: Although surgery proved to be more effective treatment, our results suggest that its average cost is greater than that of non-invasive therapy for the treatment of non-melanoma superficial cutaneous carcinomas on the lower limbs, at least after the first 2 years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 14 publications
1
27
0
1
Order By: Relevance
“…Topical therapy is also significantly more cost-effective than conventional surgery. 15 Adverse reactions to imiquimod are limited, with local reactions such as erythema, erosion and crusting being the most common. 16 More severe local reactions are associated with higher clearance rates.…”
Section: Discussionmentioning
confidence: 99%
“…Topical therapy is also significantly more cost-effective than conventional surgery. 15 Adverse reactions to imiquimod are limited, with local reactions such as erythema, erosion and crusting being the most common. 16 More severe local reactions are associated with higher clearance rates.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Aguilar et al reported that topical PDT is no more expensive than conventional surgery plus the advantage of less frequent side effects and better cosmetics (10). This economic improvement could be greater in large lesions in which surgery would be more complex.…”
Section: Discussionmentioning
confidence: 99%
“…173 In one small, retrospective study from Spain, of lesions located on the lower limbs, surgical excision of SCC in situ (n = 54) and sBCC (n = 32) provided high cure rates, but was more expensive than nonsurgical modalities following calculation of the total medical cost, as well as direct and indirect costs. 174 This study was costed on currently licensed MAL-PDT, compared with earlier studies that costed ALA-PDT. After 2 years of follow-up, a complete response was observed in 89Á5% of the PDT group, 87Á5% of the imiquimod group and 97Á5% of the surgery group, but the average total cost for each treated tumour was €536 for surgery, €214 for PDT and €229 for imiquimod.…”
Section: Practical and Health Economic Considerationsmentioning
confidence: 99%